Clinical Presentation and Outcome of Multisystem Inflammatory Syndrome in Children in Dhaka Shishu (Children) Hospital - Afroz, Shireen; Ferdaus, Tahmina; Jabbar, Abdul; Tanjila, Umme; Hasnat, Abu; Akter, Sabrina; Khondoker, Tarannum; Silvi, Tanjina Haque; Ferdous, Jannatul; Rima, Rezoana; et al. (Dhaka Shishu (Children) Hospital Journal, 2021)
Background: The increasing trend in multisystem inflammatory syndrome in children (MIS-C) during Covid-19 pandemic is alarming. Understanding the clinical course and outcome will give the clinical and public health implications of this syndrome. Objectives: This study was conducted to find out the clinical presentation, course of the disease and outcome of the children and adolescents of MIS-C. Methods: This observational study was conducted in the department of Pediatric Nephrology, Dhaka Shishu (Children) Hospital, Dhaka, Bangladesh, from August 2020 to October 2020. Total 12 children of MIS-C diagnosed according to WHO diagnostic criteria of MIS-C were included after taking written informed consent from the parents. Mean, median and standard deviation were calculated for the continuous variables. Results: The age ranged from 17 days to 13 years, 56% were male, 17% were positive for SARS-CoV-2 by RT-PCR and 4(33%) had history of the COVID-19 exposure. Organsystem involvement included bilateral pneumonia in 92%, myocarditis in 78%, swollen hands and feet in 67%, mucocutaneous involvement in 50%, diarrhea in 50%, musculoskeletal involvement in 50%, acute kidney injury (AKI) in 33% patients and acute pancreatitis in 25% patients. The median duration of hospitalization was 11 days and ICU stay was 5 days. Mean duration of fever was 8.66 days. Kawasaki’s diseaselike features were documented in 50% patients and 4 of them had elevated level of procalcitonin and troponin I. Markedly elevated C reactive protein (CRP), Ferritin and D dimer in all patients were present. All patients with cardiac involvement had left ventricular dysfunction and ejection fraction was as low as 38.5%. Coronary-artery dilatation was documented in 33%. About 67% received intensive care with oxygen support by low flow nasal cannula or face mask, 33% received vasoactive support and systemic glucocorticoid, 50% received intravenous immunoglobulin (IVIG) plus methyl prednisolone. Antiplatelet and anticoagulant therapy was given in 75% and 33% patients respectively. Out of 12 patients 2 died, the contributing cause of death included complications like hypotension, shock, myocarditis, coagulopathy and AKI. Conclusion: MIS-C led to serious and life-threatening complications especially when there are cardiac involvement, hypotension and acute kidney injury. DS (Child) H J 2020; 36(2): 87-94